Análise bibliométrica das publicações sobre Ganoderma lucidum na categoria plant sciences da base de dados Web of Science (WoS) - Santos, João Victor de Lima (2025)
Bibliometric analysis has become an essential tool for evaluating scientific output across various fields of knowledge, allowing for the identification of patterns and trends in academic literature. This study aimed to conduct a bibliometric analysis of the scientific production on Ganoderma lucidum within the Plant Sciences category of the Web of Science (WoS) database. The relevance of this research is justified by the increasing importance of this fungus in therapeutic applications, necessitating a comprehensive mapping of the state of the art. The methodology involved a systematic search for indexed papers from 1971 to 2024, the extraction of bibliometric indicators, and data analysis using the Bibliometrix and VOSviewer tools. Key aspects such as publication volume, author and institutional collaborations, emerging keywords, and academic impact were considered. The results revealed an increase in the number of publications from the 2000s onwards, with China leading the scientific output, followed by the United States and India. The main topics addressed in the literature included the pharmacological and biotechnological properties of the fungus, as well as its applications in traditional medicine. Collaboration networks indicated a predominance of research conducted in Chinese academic institutions, while international interactions remain limited. The most frequently cited author keywords included "antioxidant activity," "polysaccharides," and "cytotoxicity." The thematic evolution highlighted a transition from initial taxonomic studies to more specific investigations focusing on the bioactive properties and industrial production of the fungus. It was concluded that bibliometric analysis provides a comprehensive perspective on the research dynamics of G. lucidum, enabling the identification of knowledge gaps and opportunities for future studies.